2010
DOI: 10.3109/14767050903551442
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes for fetal echogenic bowel during the second trimester ultrasound

Abstract: In our study, almost 80% of the fetuses had an uncomplicated perinatal outcome. FEB was present as the only finding in only 5% of the fetuses with an adverse outcome. A potential association with placental abnormalities and a low prevalence of viral infections was observed. These findings may be of use in counseling parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 6 publications
2
18
0
Order By: Relevance
“…Although there have been reported associations with toxoplasmosis, parvovirus, varicella and herpes, our findings correlate with studies that have found CMV as the most likely infective agent [6,7]. These results support the suggestion that CMV may be the only virus needing further testing in cases of ultrasound-diagnosed FEB [6,7,8] in the Australian population.…”
Section: Discussionsupporting
confidence: 81%
“…Although there have been reported associations with toxoplasmosis, parvovirus, varicella and herpes, our findings correlate with studies that have found CMV as the most likely infective agent [6,7]. These results support the suggestion that CMV may be the only virus needing further testing in cases of ultrasound-diagnosed FEB [6,7,8] in the Australian population.…”
Section: Discussionsupporting
confidence: 81%
“…Nine fetuses showed hyperechogenic bowel, which was associated with ultrasound brain abnormalities in six cases, hepatomegaly in one case, and isolated findings in two cases. The significance of hyperechogenic bowel in pregnancy remains unsettled [26–28]. However, our three fetuses with hyperechogenic bowel without ultrasound brain abnormalities at 21 weeks of gestation but with moderate and severe histological brain damage presented a high CMV load in the amniotic fluid.…”
Section: Discussionmentioning
confidence: 89%
“…Group A: seven fetuses with severe cerebral damage (score [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Histological findings. Brain: CMV-positive cells were found in the cortex, white matter, germinal matrix, grey matter, ependyma, and leptomeninges.…”
Section: Resultsmentioning
confidence: 99%
“…We had no cases of toxoplasma or parvovirus infection. Other studies report a similarly low prevalence for congenital toxoplasma and CMV ranging from 0.01–1.7% . However, the studies that include screening for a wider variety of infections, such as herpes simplex virus, varicella zoster virus, parvovirus and influenza, not surprisingly, report much higher incidences of up to 20% .…”
Section: Commentmentioning
confidence: 96%